2019
DOI: 10.1016/j.fct.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory natural compounds in stress-induced depression: An alternative or an adjunct to conventional antidepressant therapy?

Abstract: The interplay of chronic stress, neuroinflammation and altered immune reactivity has been shown to be important for the pathophysiology of brain disorders such as schizophrenia, depressive disorders and post-traumatic stress disorder. This immuno-inflammatory theory has been extensively studied in the past three decades leading to the formation of the integrative discipline of psychoneuroimmunology. Targeting of the central nervous system by conventional pharmacotherapeutic methods is mainly through modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 86 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…In the past year, the academic interest in these disorders has been growing due to the COVID-19 pandemic and the related upsurge in anxiety and depression [36]. Pharmacotherapy is effective, but, at the same time, it carries the risk of side effects and dependence [37]. Hence, the search for herbal remedies for neuropsychiatric disorders continues to go on [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the past year, the academic interest in these disorders has been growing due to the COVID-19 pandemic and the related upsurge in anxiety and depression [36]. Pharmacotherapy is effective, but, at the same time, it carries the risk of side effects and dependence [37]. Hence, the search for herbal remedies for neuropsychiatric disorders continues to go on [38].…”
Section: Discussionmentioning
confidence: 99%
“…Depressive disorders may be triggered by chronic inflammation in brain associated with chronically increased levels of cytokines or other inflammatory mediators [69]. Such elevation induces a chain of endocrine reactions leading to neurotoxicity [70]. As neuroplasticity plays a significant role in the onset of depression, less neuroplasticity is associated with greater visibility of symptoms [71].…”
Section: Depressionmentioning
confidence: 99%
“…The metabolic phenotype of PTSD may be caused partially by glucocorticoid hypersensitivity, which may affect inflammation, insulin resistance, oxidative stress, and energy deficiency [79]. PTSD patients have suppressed HPA axis activity, which progressively leads to increased catecholamine levels, corticotropin-releasing factor (CRF), and reduced cortisol levels [45,47,80]. A report by Heim C et al, 2008, found that the childhood exposure to severe abuse leads to sustained stress responses through persistent CRF-receptor activity in the later life [81].…”
Section: Neuroendocrine Disturbances and Ptsdmentioning
confidence: 99%